PEDAGOGICAL CONDITIONS FOR TEACHING THE RULES OF LABOR PROTECTION AND TECHNICAL SAFETY IN HIGHER TECHNICAL EDUCATION - Numonjonov Shokhzod Dilshodjon ugli (American Journals, 2023)
In the new Uzbekistan, the education of future personnel who have matured in every possible way, are based on healthy competition and have acquired modern technologies is one of the most important directions of state policy.
Keywords: Pedagogical condition, technical safety, modern methods, modern technologies, experimental work.